Designs for graphs with six vertices and ten edges - A. D. Forbes; T. S. Griggs; K. A. Forbes (Electronic Journal of Graph Theory and Applications (EJGTA), 2019)
The design spectrum has been determined for two of the 15 graphs with six vertices and ten edges. In this paper we completely solve the design spectrum problem for a further eight of these graphs.